2012
DOI: 10.1038/oby.2012.120
|View full text |Cite
|
Sign up to set email alerts
|

Sitting and Supine Esophageal Pressures in Overweight and Obese Subjects

Abstract: Esophageal pressure can be used to approximate pleural pressure and might be clinically useful, particularly in the obese e.g to guide mechanical ventilator settings in critical illness. However, mediastinal artifact (the difference between true pleural pressure and esophageal pressure) may limit acceptance of the measurement, and reproducibility of esophageal pressure measurements remains unknown. Therefore, we aimed to assess the effect of body posture on esophageal pressure in a cohort of obese but healthy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
26
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 34 publications
(50 reference statements)
2
26
0
1
Order By: Relevance
“…Moreover, P TP at FRC in the supine position was negative in 7 out of 10 subjects, on average −3.3 ± 3.2 cm H 2 O, and it was still negative after correcting the value for the weight of the mediastinum. A study in obese patients found similar results: P eso increased from 0.1 ± 2.3 cm H 2 O to 9.4 ± 3.9 cm H 2 O when changing from the upright to the supine position respectively [49]. This study showed how the influence of mediastinum and tissue on P eso was similar in obese and normal subjects.…”
Section: Interpreting P Eso Measurementsupporting
confidence: 69%
“…Moreover, P TP at FRC in the supine position was negative in 7 out of 10 subjects, on average −3.3 ± 3.2 cm H 2 O, and it was still negative after correcting the value for the weight of the mediastinum. A study in obese patients found similar results: P eso increased from 0.1 ± 2.3 cm H 2 O to 9.4 ± 3.9 cm H 2 O when changing from the upright to the supine position respectively [49]. This study showed how the influence of mediastinum and tissue on P eso was similar in obese and normal subjects.…”
Section: Interpreting P Eso Measurementsupporting
confidence: 69%
“…Th ese results point toward a relatively constant increment in Pes attributable to 'mediastinal artifact' when supine, independent of the body mass index (BMI). Moreover, elevated IAP and reduced chest wall compliance appear to explain components of the higher end-expiratory Pes values encountered in both positions among overweight/obese subjects [12].…”
Section: Nterpreting Pes Measurements: What Is Pes Really Measuring?mentioning
confidence: 99%
“…Recently, Owens et al [12] concluded that Pes measurement artifacts imposed by mediastinal weight and postural eff ects are within a clinically acceptable range. Th ese authors [12] compared the cha nges in end-expiratory Pes secondary to position changes in a cohort of overweight/obese spontaneously breathing patients with those occurring in lean subjects.…”
Section: Nterpreting Pes Measurements: What Is Pes Really Measuring?mentioning
confidence: 99%
See 2 more Smart Citations